Cooperativity between CD8+ T cells, non-neutralizing antibodies, and alveolar macrophages is important for heterosubtypic influenza virus immunity. - Brian J Laidlaw; Vilma Decman; Mohammed-Alkhatim A Ali; Michael C Abt; Amaya I Wolf; Laurel A Monticelli; Krystyna Mozdzanowska; Jill M Angelosanto; David Artis; Jan Erikson; E John Wherry (PLoS Pathogens, 2013)
Seasonal epidemics of influenza virus result in ∼36,000 deaths annually in the United States. Current vaccines against influenza virus elicit an antibody response specific for the envelope glycoproteins. However, high mutation rates result in the emergence of new viral serotypes, which elude neutralization by preexisting antibodies. T lymphocytes have been reported to be capable of mediating heterosubtypic protection through recognition of internal, more conserved, influenza virus proteins. Here, we demonstrate using a recombinant influenza virus expressing the LCMV GP33-41 epitope that influenza virus-specific CD8+ T cells and virus-specific non-neutralizing antibodies each are relatively ineffective at conferring heterosubtypic protective immunity alone. However, when combined virus-specific CD8 T cells and non-neutralizing antibodies cooperatively elicit robust protective immunity. This synergistic improvement in protective immunity is dependent, at least in part, on alveolar macrophages and/or other lung phagocytes. Overall, our studies suggest that an influenza vaccine capable of eliciting both CD8+ T cells and antibodies specific for highly conserved influenza proteins may be able to provide heterosubtypic protection in humans, and act as the basis for a potential "universal" vaccine.